Laws and societies in global contexts : contemporary approaches / Eve Darian-Smith. - Darian-Smith, Eve, 1963- (Cambridge University Press, 2013)
This work promotes a global socio-legal perspective that engages with multiple laws and societies and diverse socio-legal systems based on different historical and cultural traditions.